As causas naturais a perspectiva da arte médica no Corpus Hippocraticum - Terlizzi, Regina Helena (2016)
The Corpus Hippocraticum or Hippocratic Collection brings together a group of Greek medical treatises from V and IV centuries BC, among which we find the register of fundamental speeches from Hippocratic authors in defense of the existence of medical activity as art in Greek culture. The diversity of problems and the intensity of polemics from epistemological nature should be comprehended in the context of an intense intellectual activity, which reaches several domains of human knowledge and which characterizes the so-called Pericles century. In order to establish medicine as art, Hippocraticals must present the basis of the method which enabled them the advance in knowledge of natural causes for human diseases. As such knowledge supposes a series of notions elaborated by philosophy, cause (aitia) and nature (physis), there is an interweaving of matters and theories which positively brings both knowledge fields closer, until the point in which a categorical medical divergence is installed related to the philosophical method. The polemics, as the treatises certify, end up opposing, on one hand, those who defend the insertion of philosophical assumptions in medicine, according to which it could not go on without previous knowledge regarding human nature and the elements which constitute it; on the other hand, those who affirm that the existence of an old medicine which long ago could find its own means of investigation, therefore, should be considered standalone related to philosophy. As to better know the arguments level involved in these discussions, we will analyze four Hippocratic treatises where epistemological matter are approached in a more specific way: On the sacred disease, The art, On ancient medicine, On the nature of man